POLICIES ON GENDER-BASED SEGREGATION AND SEXUAL HARASSEMENT IN TRANSJAKARTA: A Q-METHODOLOGY STUDY - Syaifullah, Alfarel Ridwan (Pena Wimaya, 2025)
As the backbone of the metropolitan citizen’s mobility activities, public transportshould be a safe space from sexual harassment. Various efforts have been taken by thegovernment and service providers, such as gender-based space segregation in the form of “Women-Only Space”. Yet, sexual harassment still haunts public transportation users to this second, indicating that the current initiatives are partially ineffective. With the evolving understanding of gender and the acts of sexual harassment, a study of the implementation of “Women-Only Space” becomes crucial. Using Transjakarta as a case study, this research applies Q-Methodology analysis to interpret the diverse perceptions of the citizens regarding the issue. Then, the research findings are validated through interviews with experts in the field of gender equality and public transportation. The results of this study shows the imperfect implementation of “Women-Only Space” and other sexual harassment interventions is caused by three factors: ambiguity in defining sexual harassment, institutional failure to enhance collective awareness of sexual harssment, and the limited scope of “Women-Only Space” itself in protecting the users. In the final part, strategic steps to improve the “Women-Only Space” policy and other initiatives are outlined to prevail over the long-term war against sexual harassments in public transportation. Keywords: Gender-Based Segregation, Public Perception, Q-Methodology, SexualHarassment, Transjakarta